The Relationship Between Sociocultural Determinants with Exclusive Breastfeeding Practices in the Working Area of Sigenti Public Health Center, Tinombo Selatan Subdistrict, Parigi Moutong Regency - Febiani Riskika; Sindi Anastasya Bawiling; Ummu Aiman; Aulia Rakhman; Nur Afia Amin; Reny Rahmawati; Nurulfuadi Nurulfuadi; Try Nur Ekawati Lukman; Devi Nadila (Journal of Global Nutrition, 2025)
The coverage of exclusive breastfeeding in Indonesia has reached only 66.1%, falling short of the global target of 70% by 2030. This indicates that breastfeeding practices remain suboptimal. This study aims to analyze the relationship between maternal knowledge, educational level, family support, and food taboos with exclusive breastfeeding practices in the working area of Sigenti Public Health Center, Tinombo Selatan Subdistrict, Parigi Moutong Regency. A quantitative method with a cross-sectional approach was employed. The study population consisted of 126 mothers, from which a sample of 95 respondents was obtained using the Slovin formula and purposive sampling technique. Data were analyzed using the chi-square test with a significance level of p < 0.05. The results revealed a significant association between maternal knowledge and exclusive breastfeeding practices (p = 0.001). However, no significant relationships were found between educational level (p = 0.454), family support (p = 0.267), and food taboos (p = 0.513) with exclusive breastfeeding practices. The study concludes that low maternal knowledge is a key factor contributing to the suboptimal practice of exclusive breastfeeding. Additionally, other influencing factors such as community perceptions and the role of healthcare providers were also identified